2016
DOI: 10.1016/j.sjbs.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of ClpB/Hsp100 gene in faba bean (Vicia faba L.) plants in response to heat stress

Abstract: Heat stress adversely affects the growth and yield of faba bean crop. Accumulation of ClpB/Hsp100 class of proteins is a critical parameter in induction of acquired heat stress tolerance in plants. Heat-induced expression of ClpB/Hsp100 genes has been noted in diverse plant species. Using primers complementary to soybean ClpB/Hsp100 gene, we analyzed the transcript expression profile of faba bean ClpB/Hsp100 gene in leaves of seedlings and flowering plants and in pollen grains. ClpB/Hsp100 protein accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Analysis of Hsp100 in faba bean indicated upregulation of transcript level of ClpB/ Hsp100 gene under heat stress (38˚C) in leaf tissues. However, expression was below detection limit under control condition [30].…”
Section: Plos Onementioning
confidence: 91%
“…Analysis of Hsp100 in faba bean indicated upregulation of transcript level of ClpB/ Hsp100 gene under heat stress (38˚C) in leaf tissues. However, expression was below detection limit under control condition [30].…”
Section: Plos Onementioning
confidence: 91%
“…Presence of ClpB/HSP100 protein was detected under heat stress in Phaseolus lunatus ( Keeler et al, 2000 ). It has been observed that accumulation of ClpB/HSP100 during high temperatures increased the pollen viability in faba bean ( Kumar et al, 2015b ). Recently, in faba bean VfHsp17.9-CII (a novel HSP protein) was identified which implements heat tolerance ( Kumar et al, 2015a ).…”
Section: Genetic Approaches For Heat Tolerance In Legumesmentioning
confidence: 99%
“…The abundance of Hsp20, chaperone protein DnaJ homolog subfamily B member Os05g06440.1 and Hsp101 (Os05g44340) were upregulated across all the three genotypes under stress condition. Hsp101 is an important protein in imparting thermotolerance in bacteria, yeast and Arabidopsis ( Kumar et al, 2016 ; Kumar et al., 2020 ; Tiwari et al, 2021 ). The introduction of Arabidopsis thaliana Hsp101 (AtHsp101) into rice made the host variety more thermotolerant ( Katiyar-Agarwal et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%